2015
DOI: 10.1038/ncomms9309
|View full text |Cite
|
Sign up to set email alerts
|

A new class of tunable hypersonic phononic crystals based on polymer-tethered colloids

Abstract: The design and engineering of hybrid materials exhibiting tailored phononic band gaps are fundamentally relevant to innovative material technologies in areas ranging from acoustics to thermo-optic devices. Phononic hybridization gaps, originating from the anti-crossing between local resonant and propagating modes, have attracted particular interest because of their relative robustness to structural disorder and the associated benefit to ‘manufacturability'. Although hybridization gap materials are well known, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 26 publications
2
121
0
Order By: Relevance
“…Arranging polymer-decorated colloidal particles in periodic lattices permits the realization of two-or three-dimensional phononic crystals, in which the dispersion relations of hypersonic acoustic modes can be controlled by tuning the features of the polymer linkers and the particle-polymer interface [75,76]. This approach introduces further degrees of freedom on top of the nanostructure length scales, commonly employed to engineer phonons in hard materials.…”
Section: Phononic Metamaterials and Surface Scatteringmentioning
confidence: 99%
“…Arranging polymer-decorated colloidal particles in periodic lattices permits the realization of two-or three-dimensional phononic crystals, in which the dispersion relations of hypersonic acoustic modes can be controlled by tuning the features of the polymer linkers and the particle-polymer interface [75,76]. This approach introduces further degrees of freedom on top of the nanostructure length scales, commonly employed to engineer phonons in hard materials.…”
Section: Phononic Metamaterials and Surface Scatteringmentioning
confidence: 99%
“…We have therefore reinterpreted this band gap in terms of Fano interferences [33,66] since it is clearly the interaction between a continuum of modes (the free space waves) and a resonator [34]. Note that there are several works in the acoustic community that have tried to mix in the same frequency range the "hybridization band gap" and the Bragg gap that is due to the periodicity of the medium and mostly occurs when the lattice constant is half a wavelength [62,[67][68][69].…”
Section: Existence Of a So-called Hybridization Band Gapmentioning
confidence: 99%
“…In the field of acoustic imaging, the tailored control of hypersound (elastic waves at GHz frequencies), used for cell or other nano-compound imaging or energy conversion and harvesting (Davis and Hussein, 2014;Della Picca et al, 2016), is emerging as one of the most promising applications of energy trapping and signal enhancement through metamaterials. Furthermore, at this small scale, novel nanofabrication techniques deliver the tailoring possibilities required for graded devices (e.g., Alonso-Redondo et al, 2015;Rey et al, 2016). Among the possible resonant metasurface designs for elastic waves proposed in recent years (e.g., Baravelli and Ruzzene, 2013;Miniaci et al, 2015;Lee et al, 2016;Matlack et al, 2016;Galich et al, 2017;Tallarico et al, 2017), the one made of a cluster of rods (the resonators) (Pennec et al, 2008;Wu et al, 2008;Achaoui et al, 2011;Colombi et al, 2016c) on an elastic substrate has revealed superior characteristics and versatility of use in particular toward the fabrication of graded design.…”
Section: Introductionmentioning
confidence: 99%